Is rituximab sub‐optimally dosed in indolent B cell lymphoma?. (2nd May 2016) - Sawalha, Yazeed; Rouphail, Basel; Jia, Xuefei; Dean, Robert M.; Hill, Brian T.; Jagadeesh, Deepa; Pohlman, Brad L.; Smith, Mitchell R.
Abstract : Rituximab pharmacokinetics are affected by gender, age and weight and can affect outcomes in aggressive B cell lymphoma. Less is known about the pharmacokinetics of rituximab in indolent B cell lymphoma (iNHL). We analysed the effects of gender, age, weight and body surface area on the outcomes of 303 patients treated with first line rituximab‐based regimens for iNHL. The patients were divided into 3 treatment cohorts: rituximab only, rituximab + chemotherapy (R‐CTX) and R‐CTX followed by rituximab maintenance; furthermore, each cohort was subdivided as follicular (FL) or non‐FL, based on histology. Older males and patients with higher weight had worse outcomes when treated with R‐CTX, probably due to faster rituximab clearance. Our results concur with studies of R‐CTX for DLBCL. As this effect was not observed in patients treated with rituximab alone or R‐CTX followed by rituximab maintenance, we hypothesize that higher rituximab levels reached with weekly rituximab and/or prolonged exposure achieved with maintenance therapy exceed the therapeutic threshold, even with faster clearance, which nullifies the negative effect of higher weight and male gender. In conclusion, under current practices, a subset of patients with iNHL, i.e., FL treated with R‐CTX, may be sub‐optimally dosed with rituximab.